Faktor-Faktor yang Mempengaruhi Pemintaan Sayuran pada Rumah Tangga di Kelurahan Kadia Kecamatan Kadia Kota Kendari - Nurul MF, Muthiary; Fausayana, Ine; Yusria, Wa Ode (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
This study aims to find out about the demand and factors that influence the demand for vegetables in households in Kadia Village, Kadia District, Kendari City. This research was conducted in Kadia City Kendari Regency with a sample of 99 respondents who were determined by purposive random sampling. The results showed that: Demand for vegetables in households in Kadia Kadia Village, Kendari Regency, had an average consumption of vegetables of 7.94 kg with a frequency of average vegetable consumption of 16.65 times a month and factors affecting demand for vegetables in households in Kadia Kadia Village, Kendari Regency, vegetable prices, price of tempeh / tofu, price of eggs, price of chicken meat, price of fish, number of family members, and family income. The results of the t-test analysis found that only the variable vegetable prices and chicken meat prices were significant at the 90% confidence level.